Relationship between the Safe Benzene Concentration with Blood Profile of Printing X Surabaya Workers - Aisyah Noor Shofi Hanifah; Abdul Rohim Tualeka; Dani Nasirul Haqi; Syamsiar S Russeng; Pudji Rahmawati; Ahsan Ahsan; Indri H Susilowati (Institute of Medico-legal Publications Pvt Ltd, 2020)
Introduction : Benzene is a volatile compound and widely uses as a solvent. In its work process, printingindustry used materials containing benzene. One of the target organs of benzene exposure is bone marrow.Therefore, the effect of benzene exposure is damage to the blood formation system.Methods : This research was an observational study with a quantitative approach and cross-sectional design.Subjects used 11 workers population of printing X Surabaya. All variables were analyzed by using rankspearman correlation.Result: The test results showed that most of the levels of benzene exposure exceeded the determined LimitValue. A total of 6 (64%) workers worked ≥ 10 years. The test results revealed significant benzene exposurewith changes in HCT and MCHC values. The average safe concentration of benzene is 0.01868. The resultsof safe C testing with blood profile showed that significant for safe C Benzene with red blood cells RBC andHCT (p<0,05).Conclussion : The results of the calculation of safe C benzene and blood profile of workers showed asignificant relationship between safe C and RBC and HCT. There was no significant relationship in WBC,HGB, MCV, MCH, MCHC.